Fungsi Dinas Komunikasi dan Informatika Kota Kupang dalam Memberantas Informasi Palsu di Media Sosial - Roland Costa; Saryono Yohanes; Cyrilius Wilton Taran Lamatoro (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The development of information technology and social media has accelerated the dissemination of information, but it has also increased the circulation of false information or hoaxes, which may create public unrest and misinformation. This study analyzes the role of the Kupang City Department of Communication and Informatics in combating false information on social media and identifies factors hindering the implementation of its functions. Using empirical legal research with a socio-legal approach, data were collected through interviews, observations, and documentation at the Department and analyzed descriptively and qualitatively. The findings show that the Department has carried out its role through the Kota Kabas Hoax program, information verification and clarification, public digital literacy promotion, and collaboration with the police, academics, media organizations, and related institutions. These efforts reflect the implementation of local government authority in maintaining public information quality and preventing hoax dissemination in the digital sphere. However, several obstacles remain, including limited competent human resources, inadequate facilities and infrastructure, and low public legal awareness and digital literacy. Therefore, strengthening human resources, improving facilities, and optimizing digital literacy programs are necessary to enhance the effectiveness of combating false information on social media.